The Profile of Generic Science Skills of Pre-Service Elementary School Teacher Education of Riau University - Alpusari, Mahmud; Putra, Riki Apriyandi (Proceedings of the UR International Conference on Educational Sciences, 2018)
The purpose of this research was tofind out the profile of Generic Science Skills of Pre-Service Elementary School Teacher Education with the level of comparison and the development of generic science skills ofearly-year students,middle-year students, and final-year students. The subject of this research wasthe students of Elementary School Teacher Education Study Program consisted of 80 students that have been taken by usingStratified Sampling technique in the academic year of 2011 to 2014. The resultsof the profile of generic Science skills of Pre-Service Elementary School Teacher Educationbased on level/ academic yearshowed that the Logical Frame skill and cause-effect law skill have increased yearly.Then, the Indirect Observationskill and the awareness of scale skill have decreased. While, other skills have change dimpermanently.The changes of Generic science skills on every level of studentswere caused by some factors either internal or external factors.